Implementasi E-Government di Kabupaten Wonosobo - Dewi, Mega Hayuning Puspa; Sulandari, Susi; Rostyaningsih, Dewi (Journal of Public Policy and Management Review, 2014)
Policy e-goverment reference to presidential instruction no 3 / 2003 which requires the whole range of minister for government and regional governments moreover, there were blueprint e-government program as improve the quality ofpublic services, melelui technology it the emergence of kepemerintahan clean, transparent and able to answer charges change by effective and repairs organization, a system of management and the process of workingkepemerintahan.One of them by making website of the local government.In fact in the county of wonosobo this website, not in use to the utmost proven links with a lot of empty so that the information in give not optimal.In seeing the implementation of e-government district wonosobo is seen from first shared purpose output and impact and the second was process.The implementation of e-government in achieving its goal not regardless of factorsaffecting this policy.Based on theories van meters and van horn inferred factors impeding of resources, communication disposition, external environment. The research used by the researchers is the kind of qualitative descriptive study. By selecting informants considered the most know (non probability sampling), then use the snowball sampling. Later this research attempts to describe the existing problems and analysing a conclusion which is absolute.On the implementation of e-Government in Wonosobo Regency, procurement website has been held since in 2009, but the number of empty links make an impact/benefits generated insufficient. This is caused by a lack of human resources, implementor, disposition and the external environment.Based on the results of the implementation of the e-government policy in Wonosobo Regency views his purpose and process of this policy is insufficient and will still need revamping. The authors provide recommendations in the form of: (1) the addition of the appropriate number of staff (2) socialization in order for the community to know about this policy (3) additions to the budget allocation for the e-government policy (4) enhance the commitment of the implementor (5) create other accounts on social media in order to increase public participation.